2014
DOI: 10.1002/2014gl059683
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of electron temperatures in the Mars ionosphere and their effects on electron densities

Abstract: Observations of peak electron densities in the Mars ionosphere are well fit by a simplistic theory that assumes the electron temperature, Te, at the peak remains constant as solar zenith angle, χ, changes. However, Te ought to vary with both altitude and χ. Here we use an existing numerical model of ionospheric energetics, which includes both vertical and diurnal variations in temperatures, to predict that Te at the ionospheric peak is relatively independent of χ. This model accurately predicts the observed de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 38 publications
(70 reference statements)
3
30
2
Order By: Relevance
“…All existing measurements of the O2+ dissociative recombination coefficient, α , at 300 K agree within 15% [ McLain et al , ]. Meanwhile, since α is proportional to electron temperature to the power of −0.7 [ Peverall et al , ; McLain et al , ], the reduced value of α reported above would then imply an exceptionally high electron temperature of ≈7.2 × 10 3 K, which, at ionospheric altitudes, is not predicted by any existing models [e.g., Matta et al , ; Withers et al , ]. Strictly speaking, α in equation refers to the O2+ dissociative recombination coefficient weighted by electron density squared.…”
Section: Modeling Of the Day‐to‐night Transportmentioning
confidence: 78%
“…All existing measurements of the O2+ dissociative recombination coefficient, α , at 300 K agree within 15% [ McLain et al , ]. Meanwhile, since α is proportional to electron temperature to the power of −0.7 [ Peverall et al , ; McLain et al , ], the reduced value of α reported above would then imply an exceptionally high electron temperature of ≈7.2 × 10 3 K, which, at ionospheric altitudes, is not predicted by any existing models [e.g., Matta et al , ; Withers et al , ]. Strictly speaking, α in equation refers to the O2+ dissociative recombination coefficient weighted by electron density squared.…”
Section: Modeling Of the Day‐to‐night Transportmentioning
confidence: 78%
“…Withers et al . [] came to an opposite conclusion based on simulations of the dependence of the peak electron density with temperature using the Boston University ionosphere model [e.g., Martinis et al ., ; Matta et al ., ]. However, they assumed an electron temperature profile based on extrapolations of the Viking lander measurements to lower altitudes [ Mendillo et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Physically, this rate can vary with the solar zenith angle (SZA) as solar wind normal pressure onto the planet is smaller with increasing SZA. In addition, the altitude of the Martian dayside electron density peak is also roughly proportional to a cosine function of SZA [e.g., Hantsch and Bauer , ; Withers , ; Withers et al , ], which can be explained by Chapman theory [ Chapman , ]. As a result, the magnetic pileup boundary (MPB) is closer to the planet near the subsolar point and at higher altitudes at larger SZA [e.g., Vignes et al , ; Crider et al , ; Nagy et al , ].…”
Section: Resultsmentioning
confidence: 99%